Dosage Optimization of Artificial Digestive Enzymes in Feed to Improve The Digestibility and Growth of Osphronemus gourami - Bokau, Rietje J.M; Febriani, Dian; Indariyanti, Nur; Rakhmawati, Rakhmawati (Aquacultura Indonesiana, 2018)
One of the obstacles often encountered in the cultivation of gourami is  a relatively slow rate of growth compared with other freshwater fishes. This slow growth is partly due to the incomplete and unbalanced nutritional content and the low ability of the fish to digest a certain  type of feed materials. The ability to digest fish feed types depends on the quality and quantity of feed and enzymes present in the digestive tract. The enzymes released by the glands in the gut have the function to digest food elements. Among the enzymes involved in digestion are amylase, protease, lipase, cellulase, pectinase, and pullulanase.  To improve digestion, the use of artificial enzymes in certain doses is combined with natural food such as papaya to optimize the dose of artificial enzymes. The use of papaya is already widely used as a food supplement, especially in the  gourami grow-out culture. Aside from being natural food, papaya leaves can also serve as a natural source of digestive enzymes. The objective of this study is to determine the optimal dose of artificial enzymes added to feed which can improve the digestibility and growth of gourami. In this study, treatments of artificial feeding of gourami are used with the addition of artificial enzymes amounting to 1% (A), 2% (B), 3% (C), papaya leaves and pellets (D), and pellets alone (E).  Results after two months rearing showed that the digestibility of feed supplemented with natural enzymes in papaya (papain) can be further improve optimized by the addition of artificial digestive enzymes in a dose of 3% of the weight of the feed. Fish of this treatment group  showed  faster growth compared with other treatments.